Factors Affecting the Application of Management Accounting to MSMEs - Asep Suryana; Asep Achmad Rifa'i; Deri Firmansyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
The success of an enterprise depends on many managerial decisions that are based on accounting information, in particular management accounting (MA). There are several factors that influence the application of MA in individual and group business, entrepreneurship and MSMEs. This study examines and analyzes the factors that influence the application of MA to MSMEs with HR's Skills, business characteristics, business environment and business strategy. The research sample was 34 MSMEs actors, using purposive sampling techniques. Research findings prove that human resource skills, business characteristics, business environment, and business strategy have a significant positive effect on the application of MA both individually and simultaneously. Management accounting seems to continue to be a scientific tool for managers to carry out operations, control and decision-making in a satisfactory way. The effectiveness of implementing MA is increasingly important to improve operating efficiency and management performance.